Prioritization and resource allocation in the context of the COVID-19 pandemic: recommendations for colorectal and pancreatic vancer in Germany - Lugnier, Céline; Sommerlatte, Sabine; Attenberger, Ulrike; Beer, Ambros J.; Bentz, Martin; Benz, Stefan R.; Birkner, Thomas; Büntzel, Jens; Ebert, Matthias; Fasching, Peter; Fischbach, Wolfgang; Fokas, Emmanouil; et al. (Oncology research and treatment, 2024)
In the context of the COVID-19 pandemic, there has been a scarcity of resources with various effects on the care of cancer patients. This paper provides an English summary of a German guideline on prioritization and resource allocation for colorectal and pancreatic cancer in the context of the pandemic. Based on a selective literature review as well as empirical and ethical analyses, the research team of the CancerCOVID Consortium drafted recommendations for prioritizing diagnostic and treatment measures for both entities. The final version of the guideline received consent from the executive boards of nine societies of the Association of Scientific Medical Societies in Germany (AWMF), 20 further professional organizations and 22 other experts from various disciplines as well as patient representatives. The guiding principle for the prioritization of decisions is the minimization of harm. Prioritization decisions to fulfill this overall goal should be guided by (1) the urgency relevant to avoid or reduce harm, (2) the likelihood of success of the diagnostic or therapeutic measure advised, and (3) the availability of alternative treatment options. In the event of a relevant risk of harm as a result of prioritization, these decisions should be made by means of a team approach. Gender, age, disability, ethnicity, origin, and other social characteristics, such as social or insurance status, as well as the vehemence of a patient’s treatment request and SARS-CoV-2 vaccination status should not be used as prioritization criteria. The guideline provides concrete recommendations for (1) diagnostic procedures, (2) surgical procedures for cancer, and (3) systemic treatment and radiotherapy in patients with colorectal or pancreatic cancer within the context of the German healthcare system.
Online veröffentlicht: 14. März 2024
Gesehen am 27.01.2025